Investigation of porcine circovirus type 2 and porcine circovirus type 3 infections based on dual TaqMan fluorescent quantitative PCR method and genetic evolutionary analysis of these two viruses - Cao, Mengxiang; Wei, Yanwu; Shi, Weilin; Feng, Li; Huang, Liping (Frontiers in Microbiology, 2024)
Introduction: Porcine circovirus type 2 (PCV2) is the pathogen of Porcine Circovirus Associated Diseases. Porcine circovirus type 3 (PCV3) is a novel porcine circovirus associated with porcine dermatitis and nephropathy syndrome (PDNS) and reproductive failure. PCV2 is clearly pathogenic, while the pathogenicity of PCV3 remains controversial, so it is crucial to monitor the prevalence of PCV2 and PCV3 in healthy and diseased pigs to investigate the effects of PCV3 and PCV2 on the health status of pigs.Methods: Here, we developed a PCV2 and PCV3 dual TaqMan quantitative PCR (qPCR) method to test samples from healthy and diseased pigs, to clarify the differences in the positive rates and viral copy numbers of PCV2 and PCV3, and to analyze the genetic evolution and molecular characterization of the viral genomes obtained with sequence alignment and phylogenetic analysis, homology and structural analysis of Cap proteins, and selection pressure analysis.We successfully established a dual TaqMan qPCR method for PCV2 and PCV3 with good repeatability, specificity and sensitivity. In total, 1385 samples from 15 Chinese provinces were tested with the established qPCR. The total positive rates were 37.47% for PCV3 and 57.95% for PCV2, and the coinfection rate for was 25.49%. The positive rates of PCV3 and PCV2 in 372 healthy pigs were 15.05% and 69.89%, respectively, and the coinfection rate was 12.90%. The positive rates of PCV3 and PCV2 in 246 diseased pigs were 55.69% and 83.33%, respectively, and the coinfection rate was 47.97%. Eighteen PCV3 genomes and 64 PCV2 genomes were identified, including nine each of the PCV3a-1 and PCV3b genotypes, eight of PCV2a, 16 of PCV2b, and 40 of PCV2d. The amino acid identity within the PCV3 Cap proteins was 94.00%-100.0%, whereas the PCV2 Cap proteins showed an identity of 81.30%-100.0%. PCV3 Cap was most variable at amino acid sites 24, 27, 77, 104 and 150, whereas PCV2 Cap had 10-13 unique sites of variation between genotypes.Discussion: These results clarify the prevalence and variations of PCV2 and PCV3 in healthy and diseased pigs, which will provide a basis for the prevention and control of the two viral infections.